A new species of poison frog (Amphibia: Dendrobatidae) from the Andean mountains of Tolima, Colombia - Bernal, Manuel Hernando; Luna-Mora, Victor Fabio; Gallego, Oscar; Quevedo, Alonso (Zootaxa, 2007)
We describe a new species of poison frog of the genus Ranitomeya from the Andean mountains of Tolima, Cordillera Central of Colombia. The new species can be distinguished from all other dendrobatids by its distinctive color pattern in combination with its small size and advertisement call. The maximum adult snout vent length is 17.39–18.91 mm, its dorsal surface is brown, head with a metallic yellow-bronze color, ventral surfaces overall brown dark with or without bluish green spots. This new species is syntopic with Ranitomeya dorisswansonae, but readily distinguishable by color pattern and foot morphology.